BODY IMAGE PERCEPTION AMONG FIRST GENERATION CHINESE MIGRANTS IN ITALY. (June 2018) - Casini, C.; Castellini, G.; Boddi, M.; Ricca, V.; Galanti, G.; Modesti, P.A.
Abstract : Objective: In Italy, hypertension and diabetes prevalence in the Chinese community was found to be higher than in the host population. Overweight was associated with hypertension and diabetes, thus highlighting the importance of monitoring weight in prevention strategies. Considering that body size preference may be an important factor in motivating individuals to lose weight, information about this determinant among Chinese migrants is necessary. The goals of this study were to explore ethnic differences on body image perception, to determine the association with BMI, hypertension and diabetes, and to investigate the effect of the time spent in Italy. Design and method: Cross sectional study enrolling 1500 first generation Chinese migrants (aged 18–59 years), and 300 native Italians. Participants were requested to select the two silhouettes (Pulvers' figure rating scale) closest to how they perceived themselves (current) and to how they would have preferred to look like (preferred). Comparisons were performed by multivariable adjusted regressions. Results: Chinese participants had a smaller BMI than Italians both for both men and women (OR 0.78; Cl 95% 0.69 to 0.94). Among Chinese, BMI was not affected by years spent in Italy (10 ± 5 years). Chinese chose significantly thinner current (OR 0.34;Cl95%0.26 to 0.43 for men, and 0.64;0.54 to 0.76 for women) and preferred (OR 0.44; 0.35 to 0.56 and 0.73;0.60 to 0.89 respectively) silhouettes than Italians. Perceived current body size (current silhouette) was correlated with BMI, hypertension and type 2 diabetes both among Chinese and Italians (Spearman's correlation p < 0.001 for all). Preferred silhouette was thinner than current silhouette for both men and women in both ethnic groups. Among Chinese, preferred silhouette was not correlated with the time (percentile) spent in Italy (Spearman's correlation p = 0.46). However, at multivariate adjusted linear regression a trend for the time (years) spent in Italy was observed for the selection of a thinner silhouette (B coefficient  − 0.014; − 0.029 to 0.001, p = 0.054). Conclusions: For Chinese migration seems to be associated with a tendency to further enhance the preference for thinner figures, a point which could be crucial for prevention strategies in this high risk group.